Cold temperature enhances innate eosinophilic airway inflammation via transient receptor potential ankyrin1 - Dotake, Yoichi; Matsuyama, Takahiro; Machida, Kentaro; Matsuyama, Hiromi; Takagi, Koichi; Mizuno, Keiko; Kan-o, Keiko; Kuwaki, Tomoyuki; Inoue, Hiromasa; Tanaka, Kentaro (Frontiers in Immunology, 2025)
Background and objectiveAsthma exacerbations due to cold air exposure are well recognized; however, the underlying mechanisms remain unclear. We investigate the role of the transient receptor potential ankyrin1 (TRPA1) channel in cold air-induced aggravation of innate airway inflammation using a murine model of papain stimulation combined with cold air exposure.MethodsWild-type (WT) and Trpa1 knockout (KO) mice were treated intranasally with papain under different temperature conditions. Bronchoalveolar lavage fluid (BALF) and lung tissues were analyzed. The effects of the TRPA1 antagonist HC030031 were also evaluated. Additionally, human bronchial epithelial (HBE) cells were stimulated with papain and the TRPA1 agonist allyl isothiocyanate (AITC).ResultsPapain treatment increased eosinophils in BALF, and the number of eosinophils was similar in WT and Trpa1 KO mice. Papain treatment with cold air exposure in WT mice significantly increased the number of eosinophils and type-2 innate lymphoid cells and the protein expressions of IL-5, IL-13, and TSLP in BALF. However, cold air exposure failed to augment airway eosinophilia in response to papain in Trpa1 KO mice. Treatment of HC030031 replicated the findings observed in Trpa1 KO mice. AITC enhanced papain-induced TSLP production in HBE cells by increasing the intracellular calcium concentration.ConclusionsThese findings suggest that TRPA1 channels expressed in airway epithelial cells play a critical role in producing TSLP, contributing to the enhancement of eosinophilic airway inflammation mediated by innate immunity upon cold air exposure, providing valuable insights into the mechanisms underlying asthma exacerbation triggered by cold temperatures.